2007
DOI: 10.1086/511971
|View full text |Cite
|
Sign up to set email alerts
|

Observations of High‐Redshift X‐Ray Selected Clusters with the Sunyaev‐Zel’dovich Array

Abstract: We report measurements of the Sunyaev-Zel'dovich (SZ) effect in three highredshift (0.89 ≤ z ≤ 1.03), X-ray selected galaxy clusters. The observations were obtained at 30 GHz during the commissioning period of a new, eight-element interferometer -the Sunyaev-Zel'dovich Array (SZA) -built for dedicated SZ effect observations. The SZA observations are sensitive to angular scales larger than those subtended by the virial radii of the clusters. Assuming isothermality and hydrostatic equilibrium for the intracluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 35 publications
4
117
0
Order By: Relevance
“…The SPT team found good agreement between the X-ray predicted signal and their SZ measurement within R 500 . Similarly, in a recent study, Bonamente et al (2012) used a sample of 25 clusters observed with SZA/CARMA (Muchovej et al 2007) and found an excellent agreement when modelling the SZ emission over their sample, either with the universal pressure profile from A10 or with the model from Bulbul et al (2010). Our SZ and X-ray data are in excellent agreement over the radial range (0.1-1) R 500 , providing tighter observational constraints.…”
Section: The Inner Profilesupporting
confidence: 67%
See 1 more Smart Citation
“…The SPT team found good agreement between the X-ray predicted signal and their SZ measurement within R 500 . Similarly, in a recent study, Bonamente et al (2012) used a sample of 25 clusters observed with SZA/CARMA (Muchovej et al 2007) and found an excellent agreement when modelling the SZ emission over their sample, either with the universal pressure profile from A10 or with the model from Bulbul et al (2010). Our SZ and X-ray data are in excellent agreement over the radial range (0.1-1) R 500 , providing tighter observational constraints.…”
Section: The Inner Profilesupporting
confidence: 67%
“…In parallel, SZ observations with instruments such as the SunyaevZeldovich Array (SZA, Muchovej et al 2007), the South Pole Telescope (SPT, Carlstrom et al 2011), the Atacama Cosmology Telescope (ACT, Swetz et al 2011), and Planck (Tauber et al 2010) 1 have recently started to deliver on the promise of SZ observations for cluster studies.…”
Section: Introductionmentioning
confidence: 99%
“…The SZA data were used to search for radio sources around CL J1226.9+3332 (Muchovej et al 2007). From their observations, no such objects are present within the NIKA field.…”
Section: Point Source Contaminationmentioning
confidence: 99%
“…As the SZ effect is a measure of the integrated line-of-sight electron density, weighted by temperature, i.e., the integrated pressure (see Section 2.1), it probes different properties than the X-ray emission, which is proportional to the square of the electron density. Cluster surveys exploiting the redshift independence of the SZ effect are now being conducted by a variety of instruments, including the SunyaevZel'dovich Array (SZA; Muchovej et al 2007), the South Pole Telescope (Ruhl et al 2004), the Atacama Cosmology Telescope (Kosowsky 2003) and the Atacama Pathfinder Experiment (APEX) SZ instrument (Dobbs et al 2006).…”
Section: Introductionmentioning
confidence: 99%